Survey estimates of wealth holdings in OECD countries: Evidence on the level and distribution across selected countries - Markus Jäntti; Eva Sierminska (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2007)
This paper discusses issues that arise in the comparison of estimates of wealth holdings and their distribution in light of data for selected OECD countries. We find large differences in the level of wealth, depending on whether the mean or median levels are compared across countries. Sensitivity of wealth estimates to survey design are evident in that even within countries, these ranking of two different surveys depends on how central tendency is measured. Comparisons of the composition of household wealth based on secondary data, as well as the distribution of net worth, are difficult because comparable data are scarce. The evidence suggests that country ranking by level of net worth inequality is similar to that by income inequality, and that net worth inequality has tended to increase across the countries we examine.
Keywords: D31; 330; net worth; wealth level; wealth inequality; Vermögen; Vermögensverteilung; OECD-Staaten